Preparation and characterization of a silica‐based magnetic nanocomposite and its application as a recoverable catalyst for the one‐pot multicomponent synthesis of quinazolinone derivatives. (13th September 2015) - Maleki, Ali; Rabbani, Mahboubeh; Shahrokh, Shirin
Abstract : An environmentally benign magnetic silica‐based nanocomposite (Fe3 O4 /SBA‐15) as a heterogeneous nanocatalyst was prepared and characterized using Fourier transform infrared and ultraviolet–visiblediffuse reflectance spectroscopies, scanningelectron microscopy, X‐ray diffraction, vibrating sample magnetometry and Brunauer–Emmett–Teller multilayer nitrogen adsorption. Itscatalytic activity was investigated for the one‐pot multicomponent synthesis of 2, 3‐dihydroquinazolin‐4(1 H )‐ones starting from isatoic anhydride, ammonium acetate and various aldehydes under mild reaction conditions and easy work‐up procedure in refluxing ethanol with good yields. The nanocatalyst can be recovered easily and reused several times without significant loss ofcatalytic activity . Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A magnetically recoverable silica‐based nanocomposite was prepared and characterized. Its catalytic activity was investigated for one‐pot multicomponent organic synthesis under mild reaction conditions and easy work‐up procedure.